If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 50(x + y) = 75(x + -1y) (x * 50 + y * 50) = 75(x + -1y) (50x + 50y) = 75(x + -1y) 50x + 50y = (x * 75 + -1y * 75) 50x + 50y = (75x + -75y) Solving 50x + 50y = 75x + -75y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-75x' to each side of the equation. 50x + -75x + 50y = 75x + -75x + -75y Combine like terms: 50x + -75x = -25x -25x + 50y = 75x + -75x + -75y Combine like terms: 75x + -75x = 0 -25x + 50y = 0 + -75y -25x + 50y = -75y Add '-50y' to each side of the equation. -25x + 50y + -50y = -75y + -50y Combine like terms: 50y + -50y = 0 -25x + 0 = -75y + -50y -25x = -75y + -50y Combine like terms: -75y + -50y = -125y -25x = -125y Divide each side by '-25'. x = 5y Simplifying x = 5y
| -7(-6-2z)=-7z | | 96(2+y)=80(3+y) | | 3x+1+62=90 | | 96+(2+y)=80+(3+y) | | 7x-6=2(15-x) | | B+10+2b+10=230 | | -5n+9=-3n+11 | | t^2+-30t-26=0 | | 2(5-x)=4(2x-5) | | -189=-3x+4(5x-9) | | 49y=6(8y-4) | | 8-2(x+3)=19(x+2)-9 | | 20x^5-6x^5= | | log(x+132)-log(x+2)= | | -3y=-2x+10 | | 22+n=13 | | 28x=40x-78 | | (3q-2)=16q | | 42/42p+28/42p+21/42=234 | | K-(3.2)=-6.8 | | 3a+7=-2a-3 | | 6x-16=28 | | -(7p-1)= | | [4m+9]-3[2m-5]= | | 0.28x+0.05(3000-x)=610 | | 16k+31=82-k | | 3x-12x=-180 | | 60=7t-17t | | -21=6m^2+25m | | -3+2v=v-4+2v | | 15g-8g=72+12 | | m-2(3-2m)=2m+9 |